Factor Affecting Medical Services Utilization of Insured Persons at the Phanakornsiayutthaya Hospital According to the Social Security Act B.E. 2533 - Prangprasit, Siriporn (Journal of Health Science of Thailand, 1995)
The author has studied factors affecting medical services utilization of insured persons at the Phanakornsiayutthaya Hospital according to the Social Security Act (SSA) 2533. A total of 400 insured persons working in factories registered with the PhanakornsiayutthayaHospital for medical services were included in the study by using questionnaires sent through their personnel managers. The results of this study showed that the PhanakornsiayutthayaHospital was most frequently used by insured persons, followed by private clinics and health centers. The main reason for using services at the PhanakornsiayutthayaHospital was due mainly to initial contractual agreement made by their employers. Some demographic, enabling, and satisfaction factors of insured persons using medical services at the PhanakornsiayutthayaHospital were found to be significantly related to sex, distance from residence, perceived severity of illness, past experience in medical services utilization, convenience, courtesy, and out of pocket cost as well as medical information and quality of care. Most of the insured persons wanted to include private clinics into the contractual networks. Some difficulties mentioned by insured persons under the SSA condition included inflexibility to select hospital and distance from their residences and offices. The main problems and obstacles for using medical services at the PhanakornsiayutthayaHospital were long waiting time, poor courtesy of hospital staff, and inappropriate organization of hospital services. It is, therefore, suggested from the study that government hospitals should improve their quality of services to effectively create positive image and clients’ satisfaction.